Reconstruction following full-thickness excision of abdominal wall tumors: A prospective observational study conducted in a tertiary care Government Hospital in Eastern India - Chaturvedi, Vikram; Santu Kumar Chejara; Monali Patole Mukherjee; Dipankar Mukherjee (Asian Journal of Medical Sciences, 2023)
Background: Reconstruction of abdominal wall defects following full-thickness excision of large tumors (primary or metastatic) has always been a challenge for the treating surgeon. A number of reconstructive techniques have been described in the literature, including different types of meshes, flaps, and component separation techniques (anterior and amp; posterior), with varying results. We conducted a prospective observational study of our three-layer technique of abdominal wall closure at Medical College Hospital, Kolkata, to assess the long-time success of the procedure, especially in terms of hernia rates. Aims and Objectives: Reconstruction of abdominal wall defects following full-thickness excision of large tumors (primary or metastatic) has challenged surgeons for long, with several reconstructive techniques being described, with varying results. We conducted a prospective observational study of our three-layer technique of abdominal wall closure at Medical College Hospital, Kolkata, to assess the long-time success of our procedure, especially in terms of hernia rates. Materials and Methods: Thirteen patients with abdominal wall primary and isolated metastatic tumors were included from January 2017 to January 2022 with follow-up period from 8 to 60 months. Tumors were dermatofibrosarcoma protuberans, sarcomas, desmoid tumors, and two abdominal wall metastases. All patients in our study underwent computed tomography scan, core needle biopsy, and immunohistochemistry for better surgical planning. Results: Eight patients were male and five were female with mean age of 39 years and mean defect size of 10 cm. Polypropylene mesh was used, size varying from 15×15 to 30×30 cm with average operative time of 210 min. Post-operative superficial wound infection in 2 (15%), partial flap necrosis in 1 (7.6%), and tumor recurrence in one patient (7.6%) were seen. Conclusion: For closure of such large abdominal wall defects, our three-layer reconstructive technique has shown good results in terms of zero hernia rates. We recommend our method of closure, where affordability of biological meshes, availability of expensive meshes, accessibility to plastic and reconstructive surgeons or non-acquaintance with complex closure techniques are present.